Plasma Phospholipid Omega‐3 Fatty Acids and Incidence of Postoperative Atrial Fibrillation in the OPERA Trial. Issue 5 (21st October 2013) - Wu, Jason H. Y.; Marchioli, Roberto; Silletta, Maria G.; Macchia, Alejandro; Song, Xiaoling; Siscovick, David S.; Harris, William S.; Masson, Serge; Latini, Roberto; Albert, Christine; Brown, Nancy J.; Lamarra, Mauro; et al.
Abstract : Background: Long‐chain polyunsaturated omega‐3 fatty acids (n‐3 PUFA) demonstrated antiarrhythmic potential in experimental studies. In a large multinational randomized trial (OPERA), perioperative fish oil supplementation did not reduce the risk of postoperative atrial fibrillation (PoAF) in cardiac surgery patients. However, whether presupplementation habitual plasma phospholipid n‐3 PUFA, or achieved or change in n‐3 PUFA level postsupplementation are associated with lower risk of PoAF is unknown. Methods and Results: In 564 subjects undergoing cardiac surgery between August 2010 and June 2012 in 28 centers across 3 countries, plasma phospholipid levels of eicosapentaenoic acid (EPA), docosapentaenoic acid (DPA), and docosahexaenoic acid (DHA) were measured at enrollment and again on the morning of cardiac surgery following fish oil or placebo supplementation (10 g over 3 to 5 days, or 8 g over 2 days). The primary endpoint was incident PoAF lasting ≥30 seconds, centrally adjudicated, and confirmed by rhythm strip or ECG. Secondary endpoints included sustained (≥1 hour), symptomatic, or treated PoAF; the time to first PoAF; and the number of PoAF episodes per patient. PoAF outcomes were assessed until hospital discharge or postoperative day 10, whichever occurred first. Relative to the baseline, fish oil supplementation increased phospholipid concentrations of EPA (+142%), DPA (+13%), and DHA (+22%) ( P <0.001 each). Substantial interindividual variability was observed for change in total n‐3 PUFA (range=−0.7% to 7.5% after 5 days of supplementation). Neither individual nor total circulating n‐3 PUFA levels at enrollment, morning of surgery, or change between these time points were associated with risk of PoAF. The multivariable‐adjusted OR (95% CI) across increasing quartiles of total n‐3 PUFA at enrollment were 1.0, 1.06 (0.60 to 1.90), 1.35 (0.76 to 2.38), and 1.19 (0.64 to 2.20); and for changes in n‐3 PUFA between enrollment and the morning of surgery were 1.0, 0.78 (0.44 to 1.39), 0.89 (0.51 to 1.55), and 1.01 (0.58 to 1.75). In stratified analysis, demographic, medication, and cardiac parameters did not significantly modify these associations. Findings were similar for secondary PoAF endpoints. Conclusions: Among patients undergoing cardiac surgery, neither higher habitual circulating n‐3 PUFA levels, nor achieved levels or changes following short‐term fish oil supplementation are associated with risk of PoAF. Clinical Trial Registration: URL: Clinicaltrials.gov Unique identifier: NCT00970489